At A Cost : The Real Effects of Thin Capitalization Rules - Mooij, Ruud A. (IMF Working Papers; Working Paper, 2021)
Thin capitalization rules (TCRs) aim to mitigate profit shifting by multinational corporations (MNCs) but, by raising the cost of capital for affected affiliates, can also negatively affect real investment. Exploiting unique panel data on multinational companies in 34 countries during 2006-2014, we estimate that the size of this adverse investment effect can be large, and dependent on the statutory corporate tax rate and the tightness of the safe-haven ratio. Negative investment effects are more pronounced for highly-levered firms for which TCRs are more likely to be binding.